Tumor-Derived Extracellular Vesicles: A Means of Co-opting Macrophage Polarization in the Tumor Microenvironment - Reed, Theodore; Schorey, Jeffrey; D’Souza-Schorey, Crislyn (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are a heterogeneous population of membrane-bound parcels of bioactive proteins, nucleic acids, and lipids released from almost all cell types. The diversity of cargo packaged into EVs proffer the induction of an array of effects on recipient cells. EVs released from tumor cells have emerged as a vital means of communication and immune modulation within the tumor microenvironment (TME). Macrophages are an important contributor to the TME with seemingly paradoxical roles promoting either pro- or anti-tumoral immune function depending on their activated phenotypes. Here, we discuss the influence of tumor-derived extracellular vesicles on the functional plasticity of macrophages in tumor progression.